2016
DOI: 10.3855/jidc.7196
|View full text |Cite
|
Sign up to set email alerts
|

Comparative in-vitro activity of ceftaroline against Staphylococcus aureus isolates from India

Abstract: This item has no abstract. Follow the links below to access the full text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…18 Additionally, it can reach its destination quickly. 19 All of the time-kill curves for the microorganisms tested followed a similar pattern. At 8 hours, Vancomycin displayed a bactericidal effect, as indicated by a decrease in CFU/mL of more than 3 logs relative to the original number of bacteria; however, ATCC MRSA isolates continued to thrive on NA solid media.…”
Section: Discussionmentioning
confidence: 71%
“…18 Additionally, it can reach its destination quickly. 19 All of the time-kill curves for the microorganisms tested followed a similar pattern. At 8 hours, Vancomycin displayed a bactericidal effect, as indicated by a decrease in CFU/mL of more than 3 logs relative to the original number of bacteria; however, ATCC MRSA isolates continued to thrive on NA solid media.…”
Section: Discussionmentioning
confidence: 71%
“…If the current CLSI guidelines are applied, these isolates will be classified as SDD and not as resistant. Bakthavatchalam YD et al reported a total of 13 isolates with ceftaroline MIC 2–4 µg/mL, while our study reported 14 isolates in the SDD category (2–4 µg/mL) while using CLSI 2021 criteria ( 25 ).…”
Section: Discussionmentioning
confidence: 47%
“…In January 2019, CLSI also modified the ceftaroline breakpoints and introduced the susceptible dose dependent (SDD) category for this agent, based on the recommendation by the European Medicines Agency in 2017 (High dose regimen of 600 mg every 8 h over 120 min), although this dosing regimen is not approved by the US Food and Drug Administration( 23 ). There are very few studies in India evaluating the susceptibility of S.aureus to ceftaroline and there is very little data available about the susceptibility pattern of S.aureus to ceftaroline ( 24 , 25 , 26 ). The aim of this study was to: Estimate the rate of in vitro susceptibility of ceftaroline among isolates of MRSA by E-test strip using CLSI and EUCAST breakpoints; To assess the agreement between the two guidelines for susceptibility testing of Ceftaroline; and To find the antimicrobial susceptibility pattern of MRSA isolated during the study period.…”
Section: Introductionmentioning
confidence: 99%
“…Its side effects are much lesser compared to the usual treatment regimen, i.e., glycopeptides like vancomycin and teicoplanin. Very few studies are available in world literature and in India regarding ceftaroline's susceptibility to MRSA [8][9][10]. Hence, this study was undertaken to find out the in vitro susceptibility to ceftaroline.…”
Section: Discussionmentioning
confidence: 99%